The Application of Kafā’ah and Weton in the Socio-Legal Development of Marriage Law in East Java - Abbas, Suwarto; Mukhlas, Oyo Sunaryo; Neonbeni, Randy Vallentino; Saebani, Beni Ahmad; Judijanto, Loso; Saepullah, Usep; Sistyawan, Dwanda Julisa (Nurani, 2025)
Kafā’ah (equivalence) constitutes a fundamental principle in Islamic marriage law, aimed at ensuring compatibility between the bride, the groom, and their respective guardians. In East Java, this principle intersects with the cultural practice of calculating weton a Javanese astrological system used to predict harmony and marital success demonstrating how religion and local traditions converge in shaping marital norms. This study aims to analyze the integration of weton practices into the concept of kafā’ah within the socio-legal framework of Islamic marriage law in Indonesia. Employing a qualitative approach, it draws on socio-legal analysis of primary Islamic legal sources, local customs, and state regulations. The data were obtained through document analysis, literature review, and interviews with religious leaders and community figures in East Java. The findings reveal that weton calculation is widely regarded as a cultural expression of kafā’ah, reflecting communal efforts to preserve marital harmony. Although rooted in tradition, it is often interpreted through a religious lens, thereby shaping community perceptions of marriage readiness. This dynamic interplay between Islamic jurisprudence and Javanese wisdom not only sustains local traditions but also enriches the understanding of compatibility in Indonesian marriage law. The study emphasizes the importance of incorporating cultural context into legal development, illustrating how practices such as weton serve to bridge the normative framework of Islamic law with the socio-cultural realities of Indonesia.